Analisis Perbandingan Laporan Keuangan untuk Memprediksi Kinerja Perusahaan dengan Menggunakan Metode Trend - Indri Nurafifah; Abu Darim (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to compare the 2019 and 2020 financial statements of PT Industri Jamu and Farmasi Sido Muncul Tbk using the trend method. The data studied were in the form of case studies of the 2019 and 2020 financial statements of PT Industri Jamu and Farmasi Sido Muncul Tbk. The data collection technique used was a case study. The data analysis technique used is a qualitative descriptive analysis technique. The results of this study are a review of the comparison of financial statements in 2019 and 2020 using the company trend method where later there will be several additional factors to the company’s performance which can be predicted for the profit component to continue to increase in the following year, while in 2019 and 2020 the percentage comparison uses the trend method to profit and loss in 2019 was 122%, balance sheet in 2019 was 106% and for profit and loss in 2020 was 141%, balance sheet obtained in 2020 was 111%.